Manajemen Peserta Didik Dalam Meningkatkan Budaya Disiplin Di SMP Unggulan Mukhtar Syafa’at Blokagung Banyuwangi Tahun 2022/2024 - Ikhsan Huzali; Moh. Fathul Ikhsan (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The objectives of this study are: 1) To find out the planning of students in improving the culture of discipline at Mukhtar Syafa'at Blokagung Banyuwangi Middle School. 2) To find out the coaching of students in improving the culture of discipline at Mukhtar Syafa'at Blokagung Banyuwangi Middle School. 3) To find out the inhibiting and supporting factors for student management in improving the culture of discipline at Mukhtar Syafa'at Blokagung Banyuwangi Middle School. This study uses a qualitative research approach with a descriptive qualitative research type. used to collect data in this study is through observation, interviews, and documentation. Determination of informants in this study using purposive. The data analysis used is Miles and Huberman's interactive analysis which includes data collection, data presentation, and conclusion and verification. To test the validity of the data using source triangulation. The results in this study are student management in improving the culture of discipline at Mukhtar Syafa'at Superior Middle School through planning, coaching and evaluation. While the focus of the discipline culture here is learning discipline, time discipline, worship discipline and attitude discipline.